PENGARUH STRATEGI WHOLE BRAIN TEACHING TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SEKOLAH DASAR - Ramadhani, Dini (2014)
This research was motivated by the lack of learning motivation and mathematical communication skills. One way to improve the learning motivation and mathematical communication skills of students is to use whole brain teaching strategies. The study was conducted in schools of Bandung and performed at second semester of school year 2013/2014. The population was students in fourth grade.This research aims to see the effect of whole-brain learning teaching on learning motivation and mathematical communication skills. The method of the research was a quasi-experiment with pretest-posttest control design. Instrument used was a questionnaire learning motivation and mathematical communication skills test. Data were analyzed by examining the mean difference. The results showed that there is an effect increased motivation learning and mathematical communication skills better to use whole brain teaching strategies. Research can be recommended is the use of whole brain teaching strategies must be adapted to the mathematics learning materials and psychological condition of students.